1965
DOI: 10.3181/00379727-119-30259
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hypertonic Mannitol on Renal Vascular Resistance.

Abstract: The renal hemodynamic effects of hypertonic mannitol infusions have recently become of interest. Infusions of this 6 carbon sugar alcohol appear to have the property of preventing postoperative oliguria ( 1 ) and acute tubular necrosis in cases of crossclamping of the abdominal aorta( 2,3). Experimentally, these infusions have resulted in increased total renal blood flow in hypotensive(4,S) and normotensive(6) dogs as measured by clearance techniques, and in medullary blood flow in normotensive animals as dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
2

Year Published

1968
1968
1995
1995

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 0 publications
0
15
0
2
Order By: Relevance
“…Most investigators have favored an increase in either or both rpf and PG as the major factors contributing to this beneficial effect. The postulated changes were attributed to a vasodilating effect of mannitol upon the AR vessels (11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most investigators have favored an increase in either or both rpf and PG as the major factors contributing to this beneficial effect. The postulated changes were attributed to a vasodilating effect of mannitol upon the AR vessels (11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
“…The widespread use of mannitol in clinical medicine in an effort to increase, maintain, or restore glomerular filtration rate has inspired a large number of studies which have examined the mechanism of action of this useful agent (1)(2)(3)(4)(5)(6)(11)(12)(13)(14). Most investigators have favored an increase in either or both rpf and PG as the major factors contributing to this beneficial effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the larger vessels of ischemic kidneys treated with mannitol had a mean endothelial thickness which was even less than that of normal vessels of the same size (0.45 ±0.04 and 0.57 -'0.04 / mean thickness, respectively with P of the difference <0.05). This reduction in endothelial thickness hypertonic mannitol even into nonischemic tissues (22)(23)(24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…Our data demonstrate conclusively that this suggestion is correct. A number of investigators have found that mannitol (20)(21)(22)(23) and other hypertonic solutions (24) can increase renal blood flow and decrease renal vascular resistance in the normal dog kidney. It seems plausible that renal vascular resistance is increased in the hypoperfused rat kidney, perhaps at the afferent arterioles.…”
Section: Introductionmentioning
confidence: 99%